On the possibility to observe a heavy Higgs via H⁰ →Z⁰Z⁰ →llνν decays at CMS - Levchuk, L.G.; Soroka, D.V.; Sorokin, P.V.; Voronko, M.V.; Zub, S.S. (Вопросы атомной науки и техники, 2004)
A possibility to observe with the CMS a heavy (MH  200 GeV/c²) Higgs decaying via H⁰ → Z⁰Z⁰ → llνν is studied. It is suggested that for Higgs masses close to threshold of H⁰ decay to the Z⁰Z⁰ pair. The “irreducible” background due to non-resonance production of weak boson pairs can be eliminated by a proper choice of event selection criteria leading to signature “l⁺ l⁻ + ET miss+ jets”. This observation is illustrated by PYTHIA/CMSJET simulations. For suppression of the Z+jets and tt contributions to the background, two sets of kinematics cuts are considered.